Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.7717/peerj.1907
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study on non-viral transfection of F9 (factor IX) gene by nucleofection in human adipose-derived mesenchymal stem cells

Abstract: Background. Hemophilia is a rare recessive X-linked disease characterized by a deficiency of coagulation factor VIII or factor IX. Its current treatment is merely palliative. Advanced therapies are likely to become the treatment of choice for the disease as they could provide a curative treatment.Methods. The present study looks into the use of a safe non-viral transfection method based on nucleofection to express and secrete human clotting factor IX (hFIX) where human adipose tissue derived mesenchymal stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The transfection efficiency of our protocol was comparable with some previous studies with primary cells 16,28 and eminently higher than that of studies with different kinds of stem cells and other transient transfection methods (Table 2). 24,25,27,41–43 According to flow cytometry analysis, our protocol meets clinically relevant number of cell suitable for tissue engineering and cell transplantation.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The transfection efficiency of our protocol was comparable with some previous studies with primary cells 16,28 and eminently higher than that of studies with different kinds of stem cells and other transient transfection methods (Table 2). 24,25,27,41–43 According to flow cytometry analysis, our protocol meets clinically relevant number of cell suitable for tissue engineering and cell transplantation.…”
Section: Discussionsupporting
confidence: 82%
“…25–27 Physical methods are reported with high transfection efficiency. Among the different complicated and expensive physical methods such as magnet-mediated transfection, biolistic particle delivery, or microinjection, 28–33 we decided for electroporation that is relatively easy and cheap. Here an electrical field is applied to permeabilize the cells for DNA transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, in non‐obese diabetic mice, the acute hepatic injury is induced by acetaminophen. Administration of AD‐MSC‐FIX caused an increased plasma level of FIX after 48 hr of injection and this increase remained fixed for 2 weeks (Olmedillas López, Garcia‐Arranz, Garcia‐Olmo, & Liras, ).…”
Section: Mscs As a Delivery Vehicle For Blood Disorders Gene Therapymentioning
confidence: 99%
“…We identified appropriate NF conditions that, in our 5% SRGF expanded ASC, allowed higher transfection efficiency coupled with increased cell viability, in turn leading to a significantly elevated yield of modified ASC. A different program was previously [ 17 , 41 ] defined as suitable for the ASC transfection; such discrepancy can be ascribed to the different cell buffer used for electric shock administration, as well as to MSC origin [ 41 , 43 ] or to the cell donor age [ 17 ]. Here, we also showed that increasing SRGF availability in cell expansion medium over 5% failed to provide beneficial effects on cell transfection performance.…”
Section: Discussionmentioning
confidence: 99%